1986
DOI: 10.1016/0014-5793(86)80188-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of poly(ADP‐ribose) polymerase catalysis; mono‐ADP‐ribosylation of poly(ADP‐ribose) polymerase at nanomolar concentrations of NAD

Abstract: Calf thymus and rat liver poly(ADP-ribose) polymerase enzymes, and the polymerase present in extracts of rat liver nuclei synthesize unstable mono-ADP-ribose protein adducts at 100 nM or lower NAD concentrations. The isolated enzyme-mono-ADP-ribose adduct hydrolyses to ADP-ribose and enzyme protein at pH values slightly above 7.0 indicating a continuous release of ADP-ribose from NAD through this enzymebound intermediate under physiological conditions. NH,OH at pH 7.0 hydrolyses the mono-ADP-ribose enzyme addu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Notably, this decomposition process is favored in the presence of nicotinamide, which is released upon poly(ADP‐ribosyl)ation. Previous studies under similar conditions (pH 8.0, 20 μg rat liver PARP, 100 n m NAD + , 23 °C) showed a regressing amount of pADPr ‐modified PARP after 50 min, which is consistent with the kinetics obtained for NAD + ‐induced PARP1 auto‐modification . The lower amount of p tz ADPr and premature regression of the correspondingly modified PARP1 suggest reduced compatibility, which could reflect less effective oligomerization or faster degradation of the shorter oligomers formed.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Notably, this decomposition process is favored in the presence of nicotinamide, which is released upon poly(ADP‐ribosyl)ation. Previous studies under similar conditions (pH 8.0, 20 μg rat liver PARP, 100 n m NAD + , 23 °C) showed a regressing amount of pADPr ‐modified PARP after 50 min, which is consistent with the kinetics obtained for NAD + ‐induced PARP1 auto‐modification . The lower amount of p tz ADPr and premature regression of the correspondingly modified PARP1 suggest reduced compatibility, which could reflect less effective oligomerization or faster degradation of the shorter oligomers formed.…”
Section: Resultssupporting
confidence: 85%
“…Firstly, the increasing amount of modified PARP1 and the shift to higher MW reveal an ongoing polymerization reaction upon treatment with NAD + and N tz AD + . Secondly, the subsequent regression of modified PARP1 indicates decomposition and cleavage of the pADPr ‐protein linkages, which are known to be fragile ( t 1/2 <1 h, pH 7.5) . Notably, this decomposition process is favored in the presence of nicotinamide, which is released upon poly(ADP‐ribosyl)ation.…”
Section: Resultsmentioning
confidence: 99%
“…Kun and associates have recently examined the mode ofpoly(ADP-ribose)polymerase catalysis in more detail (Bauer et al 1986). Interestingly, purified polymerase from calf thymus or rat liver synthesized unstable mono-ADP-ribose protein adducts ("initiator intermediates") when incubated at nanomolar NAD concentrations.…”
Section: Domain Structurementioning
confidence: 99%
“…NADP ÷, 3-APAD ÷ or NHD + did not exert a significant influence on pADPRT activity [4]. Bauer et al [5] reported that 3-APAD ÷ and several other NAD + analogs substituted in the pyridine base of NAD ÷ served as forward activators in the initial (ADP-ribosyl)ation reaction, whereas the elongation of ADP-ribose chains seemed to be unaffected. Deoxy derivatives of NAD + have been employed to investigate the mechanism of chain elongation.…”
Section: Introductionmentioning
confidence: 99%